2016
DOI: 10.1097/j.pain.0000000000000455
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal activity of corneal cold thermoreceptors underlies the unpleasant sensations in dry eye disease

Abstract: Discomfort in dry eye is possibly caused by an augmented ongoing activity in corneal cold neurons secondary to dryness-induced alterations in sodium and potassium channel expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
125
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 93 publications
(141 citation statements)
references
References 73 publications
(125 reference statements)
13
125
0
3
Order By: Relevance
“…55 Corneal cold thermoreceptor fibers are implicated in the regulation of basal tearing rate and have been proposed also as the source of the unpleasant dryness sensation associated with dry eye disease. 13,20,24,26 The differences in time course and characteristics of disturbances in corneal nerve activity observed in mice after PRK confirm the important role played by aberrant impulse activity in axotomized nerves for the appearance of dysesthesias following PRK 56 and lend support to the proposal that, among the different functional subclasses of corneal nerves, cold thermoreceptors are major players in the development of phantom unpleasant dryness sensation after photorefractive surgery procedures.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…55 Corneal cold thermoreceptor fibers are implicated in the regulation of basal tearing rate and have been proposed also as the source of the unpleasant dryness sensation associated with dry eye disease. 13,20,24,26 The differences in time course and characteristics of disturbances in corneal nerve activity observed in mice after PRK confirm the important role played by aberrant impulse activity in axotomized nerves for the appearance of dysesthesias following PRK 56 and lend support to the proposal that, among the different functional subclasses of corneal nerves, cold thermoreceptors are major players in the development of phantom unpleasant dryness sensation after photorefractive surgery procedures.…”
Section: Discussionmentioning
confidence: 54%
“…24 In brief, mice were killed by cervical dislocation and eyes were excised and placed in a physiological saline solution similar to tear fluid (in mM: NaCl [128], KCl [5], NaH 2 PO 4 [1], NaHCO 3 [26], CaCl 2 [2.4], MgCl 2 [1.3], and glucose [10]) and bubbled with carbogen gas (5% CO 2 and 95% O 2 ). The eye was then placed in a recording chamber and was continuously superfused with the same physiological saline solution.…”
Section: Electrophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have already shown the lack of association between DED symptoms and ocular surface signs [51] and age [52]. Reduction of the tear secretion in dry eye patients induce inflammation and peripheral nerve damage [53].…”
Section: Discussionmentioning
confidence: 99%
“…9,[17][18][19] Electrophysiological experiments in other species (cat, rabbit, guinea pig, rat) firmly established that the cornea is functionally innervated by the peripheral axons of three distinct classes of peripheral sensory receptor neurons: mechanosensory, responding only to mechanical forces; polymodal nociceptor, activated by mechanical stimuli as well as heat and a variety of endogenous and exogenous chemicals; and cold thermoreceptor neurons, primarily excited by moderate cooling and hyperosmolar solutions. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] In the present work, we performed a systematic analysis of the firing properties of the various functional classes of sensory nerve terminals innervating the adult mouse cornea and defined their functional properties and firing pattern in response to stimuli of differing modality.…”
mentioning
confidence: 99%